2007
DOI: 10.4278/0890-1171-21.6.501
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Stage-Matched and Standard Public Health Materials for Promoting Physical Activity in the Workplace: The Physical Activity Workplace Study (PAWS)

Abstract: PA stage-matched materials delivered in the workplace are efficacious for women but not men. Future interventions should explore the use of these intervention materials in conjunction with multilevel strategies, and particular attention should be paid to possible gender differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 36 publications
1
78
0
1
Order By: Relevance
“…An interesting finding was that these events happened just in intervention group receiving the SMI educational program whereas there were no significant changes in control group. These results were consisting with those reported in previous studies (38)(39)(40)(41)(42). As our study showed more than two third of participants, who underwent the protocol of educational program, progressed in their stages of change from baseline, and it was a strong point of this research when compared with results of previous studies which reported less progress in moving through stages (43)(44).…”
Section: Discussionsupporting
confidence: 83%
“…An interesting finding was that these events happened just in intervention group receiving the SMI educational program whereas there were no significant changes in control group. These results were consisting with those reported in previous studies (38)(39)(40)(41)(42). As our study showed more than two third of participants, who underwent the protocol of educational program, progressed in their stages of change from baseline, and it was a strong point of this research when compared with results of previous studies which reported less progress in moving through stages (43)(44).…”
Section: Discussionsupporting
confidence: 83%
“…This study is a secondary analysis from the Physical Activity Workplace Study (PAWS) which is reported elsewhere [21]. The study sample represents an intervention trial with null main effects, so the entire sample was collapsed for this secondary data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…This sample consisted of three groups from two separate studies: the Alberta Longitudinal EXercise ANd Diabetes Research Advancement (ALEXANDRA) study (Plotnikoff et al, 2006), and the Physical Activity Workplace Study (PAWS) (Plotnikoff et al, 2007). In the ALEXANDRA study, adults (18 years of age and older) were recruited using two strategies: recruitment from the Canadian Diabetes Association registry, and recruitment of individuals from Alberta households using a randomized digit dialing protocol.…”
Section: Design and Samplementioning
confidence: 99%